Consumers' perceptions of item-level RFID Use in FMCG: A balanced perspective of benefits and risks - Kukard, W.; Wood, Lincoln (2017)
This research explores how perceived consumer benefits affect the perceived privacy risks from implementation of Radio Frequency Identification (RFID) tags at an item-level in the Fast Moving Consumer Goods (FMCG) industry. Two new categories measure the benefits and risks: in-store and after-sales. These specific categories allow the respondents' willingness to accept RFID to be evaluated using a quantitative survey focused on the primary household grocery purchasers within the USA. The results suggest differences in perceptions of the in-store and after-sales risks and benefits of RFID use. While consumers are aware of privacy risks while using RFID technology, they would be willing to use the technology if sufficient benefits are available. This research moves the discussion away from a focus on consumer privacy issues to a balanced privacy/benefits approach for consumers and how that might affect their technology acceptance, suggesting that careful management of consumer benefits might allow FMCG firms to introduce RFID technology to support their global supply chains.